Policy paper on the improvement of the existing housing policy in the state of Perak. - Mohamed Osman, Mariana; Shuid, Syafiee; Bachok, Syahriah; Abdullah, Alias; Abdul Rashid, Khairuddin; Abdullah, Muhammad Faris; Rabe, Noor Suzilawati (Kerajaan Negeri Perak, 2015)

(untitled)
The objective of this paper is to examine the current housing policies and strategies in Perak. This paper discusses the effectiveness of Perak Housing Policy in addressing the current situation. There are varying issues signified by the local plans, but the most frequent issues mentioned are an oversupply of housing stock and the lack of an affordable house. The study found that the threshold of 20 acres was found to be irrelevant and not appropriately set as the minimum limit for low-cost housing provision. The threshold of 20 acres was irrelevent because the policy is suspectible to abuse by the developers,by the latters, inclination towards breaking or disaggregating their development into piecemeal types where each would be carried out on land pieces of 20 acres and below. Thereby, maneuvring from constructing the required low and medium low-cost housing.. The new amendment of Perak Housing Policy emphasises the contemperory issues of housing in Perak. Besides that, a revision of the penalty charged for exemption of low cost and medium low-cost house also should be made. This is because other states such as Johor and Penang were charging higher penalties compared to Perak. Perak only charged 15% of the house price for the replacement of the low-cost house forgone and 10% for medium low-cost house respectively. Thus, recommendations for the improvement of the existing state housing policy are proposed to overcome varying issues in the housing sector.